An Iodine‐Vapor‐Induced Cyclization in a Crystalline Molecular Flask. Issue 20 (6th April 2016) - Knichal, Jane V.; Shepherd, Helena J.; Wilson, Chick C.; Raithby, Paul R.; Gee, William J.; Burrows, Andrew D.
Abstract: A vapor‐induced cyclization has been observed in the host environment of a crystalline molecular flask (CMF), within which 1, 8‐bis(2‐phenylethynyl)naphthalene (bpen), a diarenynyl system primed for cyclization, was exposed to iodine vapor to yield the corresponding indeno[2, 1‐α]phenalene species. The cyclization process, unique in its vapor‐induced, solvent‐free nature, was followed spectroscopically, and found to occur concurrently with the displacement of lattice solvent for molecular iodine in CMF⋅0.75 bpen⋅2.25 CHCl3 ⋅H2 O. The cyclization occurred under mild conditions and without the need to suspend the crystals in solvent. The ability of CMFs to host purely gas‐induced reactions is further highlighted by the subsequent sequential oxidation reaction of cyclized 7‐iodo‐12‐phenylindeno[2, 1‐α]phenalene (ipp) with molecular oxygen derived from air, yielding 12‐hydroxy‐7‐iodo‐2‐phenylindeno[2, 1‐α]phenalen‐1(12 H )‐one (hipp). Abstract : A crystalline flask : The iodine‐vapor‐induced cyclization of bpen into the corresponding indeno[2, 1‐α]phenalene species ipp in the host environment of a crystalline molecular flask, [(ZnI2 )3 (tpt)2 ]⋅ x (G) (tpt=2, 4, 6‐tris(4‐pyridyl)‐1, 3, 5‐triazine, G=guest), was monitored spectroscopically. The cyclization was found to proceed under mild conditions and without the need to suspend the crystals in solvent.